1996
DOI: 10.1056/nejm199606063342304
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ploidy, Chromosome 1p, and Schwann Cells in the Maturation of Neuroblastoma

Abstract: The Schwann cells in maturing neuroblastomas differ genetically from the neuronal cells. The normal number of chromosomes in Schwann cells and the abnormal number in neuroblastic ganglionic cells suggests that Schwann cells are a reactive population of normal cells that invade the neuroblastoma. Near-trip-loidy of neuroblastoma cells and intact chromosome 1 are presumably genetic prerequisites for spontaneous organoid maturation, because we found no diploidy or chromosome 1 depletions in the neuronal cells of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
155
1
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 234 publications
(166 citation statements)
references
References 47 publications
6
155
1
1
Order By: Relevance
“…Although 1 study has suggested that the Schwann cell component of ganglioneuromas originates from the tumor itself, 33 this study was disputed by others who found evidence that the Schwann cells represent an infiltrate of normal cells in the tumor. [53][54][55] The observation that DKK3 is highly expressed in the most differentiated tumor cells as well as in the presumably normal Schwann cells, suggests a more general association of high DKK3 expression and differentiation in cells from the neuroectodermal lineage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although 1 study has suggested that the Schwann cell component of ganglioneuromas originates from the tumor itself, 33 this study was disputed by others who found evidence that the Schwann cells represent an infiltrate of normal cells in the tumor. [53][54][55] The observation that DKK3 is highly expressed in the most differentiated tumor cells as well as in the presumably normal Schwann cells, suggests a more general association of high DKK3 expression and differentiation in cells from the neuroectodermal lineage.…”
Section: Discussionmentioning
confidence: 99%
“…Ganglioneuromas, in contrast, have a strong Schwann cell component. 2 The Schwann cells are presumably of nontumor origin, 4 although this has been topic of debate. 33 This raises the question whether the high DKK3 expression in ganglioneuromas might be derived from the Schwann cell component.…”
Section: High Dkk3 Expression In Ganglioneuroma and Ganglioneuroblastmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of adult cancers, DTCs are generally considered to be metastasis precursor cells 1 CCRI, Children's Cancer Research Institute, Vienna, Austria. 2 St. Anna Children's Hospital, Vienna, Austria. 3 Department of Pediatrics, Medical University of Innsbruck, Innsbruck, Austria.…”
Section: Introductionmentioning
confidence: 99%
“…Aneuploidy is a commonly observed feature in neuroblastic tumours, and has been proposed to drive tumor development by enhancing genomic instability (Ambros et al, 1996). We reported the aneuploidies of chromosomes 3, 17, 18, 22 and X as common findings in 26 cells of patients.…”
Section: Discussionmentioning
confidence: 70%